1995
DOI: 10.1161/01.str.26.3.386
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Wall Thickness Is Associated With Prevalent Cardiovascular Disease in Middle-Aged Adults

Abstract: These data document the substantially greater arterial wall thickness observed in middle-aged adults with prevalent cardiovascular disease. Both carotid and popliteal arterial IMT were related to clinically manifest cardiovascular disease affecting distant vascular beds, such as the cerebral, peripheral, and coronary artery vascular beds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
490
4
26

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 777 publications
(536 citation statements)
references
References 20 publications
16
490
4
26
Order By: Relevance
“…In population studies, there are several noninvasive ways to assess atherosclerotic vascular damage. 15,16,20,21 PWV is one of the functional markers of vascular wall changes and mainly related to arterial elastic properties. 22 PWV is generally measured between the carotid and femoral arteries (carotid-femoral PWV).…”
Section: Discussionmentioning
confidence: 99%
“…In population studies, there are several noninvasive ways to assess atherosclerotic vascular damage. 15,16,20,21 PWV is one of the functional markers of vascular wall changes and mainly related to arterial elastic properties. 22 PWV is generally measured between the carotid and femoral arteries (carotid-femoral PWV).…”
Section: Discussionmentioning
confidence: 99%
“…A measure of the degree of atherosclerosis can be obtained using high-resolution Bmode ultrasonography to quantify arterial wall thickening. Intima-media thickness (IMT) of the carotid arteries is a marker of generalised atherosclerosis [9][10][11]. In non-diabetic subjects established cardiovascular risk factors, such as age, LDL-cholesterol, systolic blood pressure, body mass index, gender and low high-density-lipoprotein (HDL) cholesterol are associated with an increased CIMT and future CVD risk [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Preterm birth has also been associated with increased vascular resistance and arterial wall thickness, which are both associated with hypertension and adverse cardiovascular outcomes (11). For instance, a study of adolescent girls born preterm found higher brachial artery and aortic pressures, a narrower abdominal aorta, and lower peripheral skin blood flow than in girls born at term (9).…”
mentioning
confidence: 99%